The Effect of Curcuma domestica Val Extract on Phagocytic Activity of Macrophage in Listeria monocytogenes Inoculated BALB/C Mice - Pangestika, Dini; Mirani, Erna; Mashoedi, Imam D. (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Cellular imunological respond is started by macrophage activity as Antigen Presenting Cell, processing antigen in such a way that emerge interactions among immune cells. Listeria monocytogenes infection often used as an example to demonstrate the immune response to the intracellular bacteria. Curcuma has been proven in vitro to have immunomodulatory effect to improve the function of T cell, NKcell, macrophage, and splenocyte. Thus, it is presumed that curcuma extract may influence macrophage phagocytic activity. The aim of this research is to find out whether there is a difference between macrophage of mice inoculated with Listeria monocytogenes after treatment of curcuma extract in stepped dose compared with control.Design and Method: This laboratory experimental research used a Post-Test Only Control Group Design method. The samples were 20 males of balb/c mice. The mice were divided into 4 groups adopted for a week before the treatments for 20 days. The groups consist of control group, group I (receiving 0.13mg/day of curcuma extract), group II (receiving 0.26 mg/day of curcuma extract, group III (receiving 0.52mg/day curcuma extract). Mice were inoculated with Listeria monocytogenes on day 15. After isolation, the macrophage was desensitized using latex beads and observed under the microscope. The data were analyzed using One way Anova test was followed by Post hoc test using SPSS 15 programme.Result: Index of macrophage phagosytosis in control group, group I, II,II were 0.914±0,27, 1.940±0,42, 2.914±0.56, 1.30±0.31 respectively. One Way Anova test showed a difference among each of groups P<0.05 except for group I and II.Conclusion: Curcuma treatment can increase macrophage phagocytic activity on balb/c mice inoculated with Listeria monocytogenes (Sains Medika, 4(1):63-70).